Influence of Cooking Methods on Consumers' Juiciness Acceptability and Palatability of Broiler Chicken Meat - E F Fabiyi (Journal of Agricultural Extension, 2015)
Consumers' juiciness acceptability and overall palatability of 8 - 10 week old broiler chicken meat cooked by boiling and by roasting were evaluated. A 6- person trained and experienced consumer sensory pahel was used in the evaluation. Panelists scored samples from each cooking method according to a 5 - point descriptive scale. The results of the evaluation show that both cooking methods produce acceptable juiciness. Boiled broiler chicken however has a higher score for overall juiciness acceptability. Boiled broiler chicken meat also scored higherjuiciness desirability than the over all desirability of roasted broiler chicken meat. Although meat from both cooking methods produced acceptable juiciness the boiled one is preferred to roasted one and could be explored to get more consumer satisfaction.